(untitled) (Вестник КазНУ. Серия Экономическая, 2016)
In this article we analyze the way of innovative products introduction of many commercial banks, and also the introduction of foreign innovations with a focus on the practices, which helps to accelerate operational process. The new banking products and services are introduced by first class leading banks in order to increase the relevance of bank. By the way, in order to maintain its leadership, the banks are proceeding improvement of new products and services for its clients. It considers first introduction and use of new advanced equipment and technology. In this article we considered the concepts of banking innovation and also the different interpretations of this concept. Thus, credit institutions not only care about preserving, but also the increase of capital of its clients by continuously offering new products and services that contribute to the development of business activity of the people. The article also describes issues and recommendations for improvement of innovative banking products.